Co-cultivo de embriões bovinos com células-tronco adultas derivadas de tecido adiposo - NASCIMENTO, Hamilton Silva do (Universidade Federal do Pará, 2014)
The in vitro embryo production (IVP) is a biotechnology used to increase the reproductive potential of genetically superior animals, embryos produced in vitro are inferior in quality when compared in vivo. Techniques trying improve the rates of in vitro produced embryos. One technique is the co-culture system using somatic cells that remove toxic metabolites and protect against oxidative stress. Mesenchymal stem cells derived from adipose tissue (CTA) are multipotent cells that secrete growth factors and cytokines. The stem cells were used in in vitro co-culture of bovine embryos at different concentrations in order to improve the protocol PIVE. CTAs underwent differentiation into three mesenchymal lineages, and was performed immunophenotyping of specific membrane markers of MSCs. The cleavage rate was assessed on the second day after fertilization and blastocyst rate on the seventh day when they were stored for counting the total number of cells and gene expression. The results were analyzed by ANOVA, T-test and post-test of Fisher, adopting a significance level of 5%. Treatment of co-cultivation with CTAs significantly influenced the formation of the blastocyst, the total number of cells in embryos and correlated gene expression pluripotency and carbohydrate metabolism. These results showed increased production rate and quality of embryos produced in vitro co-culture with CTAs compared to co-culture with granulosa cells. These results also indicate that the constant presence of CTAs in co-culture is superior to conditioning with CTAs. Checked the effects of CTAs can occur through soluble factors or via exosomes secreted by CTAs. Future studies are needed to clarify the possible cause for positive effects observed in this work by the CTAs in co-cultivation.